ESG INVESTING: IMPACT ON CORPORATE BEHAVIOR AND FINANCIAL PERFORMANCE - Khalil Zaman; Juliana Kadang; Amir Raza (Journal Markcount Finance, 2026)
Environmental, Social, and Governance (ESG) investing has gained substantial prominence as investors increasingly integrate non-financial criteria into capital allocation decisions. This shift reflects growing concerns about climate change, social responsibility, and corporate governance failures, alongside the belief that ESG-oriented firms may exhibit superior long-term performance. Despite widespread adoption, debate persists regarding the extent to which ESG investing influences corporate behavior and whether it delivers measurable financial benefits. This study aims to examine the impact of ESG investing on corporate behavior and financial performance, focusing on how ESG pressures shape strategic decision-making, risk management, and operational practices, as well as their implications for firm profitability and market valuation. The research seeks to clarify whether ESG integration functions primarily as a value-creation mechanism or as a reputational and compliance-driven strategy. The study employs a qualitative analytical approach based on secondary data, including peer-reviewed journal articles, corporate sustainability reports, financial performance indicators, and global ESG rating databases. The findings indicate that ESG investing encourages greater transparency, improved governance practices, and more sustainable operational strategies. The study concludes that ESG investing acts as a catalyst for responsible corporate behavior while offering potential financial advantages when supported by credible metrics, regulatory clarity, and strategic integration.